Sitotaksonomi Marga Adiantum Di Gunung Merapi, Lawu Dan Dataran Tinggi Dieng = Cytotaxonomy Of Adiantum Genus In Merapi Mountain, Lawu Mountain And Dieng Plateli - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT The aims of the study were to know ploidy level and reproduction type of genus Adiantum in Merapi mountain, Lawu moutain and Dieng plateu. Materials used in this study were 61 native individuals of seven species of Adiantum Genus (Adiantum tenerum, A. philippense, A. concinum, A. diaphanum, A. excisum, A. hispidulum, A. raddianum)â¢ Samples of the chromosome numbers were obtained from root tips and croziers, using squash methods. Reproduction type was determined by counting the number of spores in each sporangium. The results showed that Adiantum philipense have only a triploid level and tetraploid level was found in Adiantum excisum. Another species had various ploidy levels, i.e. Adiantum tenerum (2x & 3x)